Macrobending Multimode Plastic Optical Fiber Coated with PANI-PVA composite as a pH sensor: Ali Yunus Rohedi, Rizqi Nur Ainun, Iim Fatimah, Nurrisma Puspitasari, S Sudarsono, Gatut Yudoyono - Ali Yunus Rohedi Ali Yunus Rohedi; Rizqi Nur Ainun Rizqi Nur Ainun; Iim Fatimah Iim Fatimah; Nurrisma Puspitasari Nurrisma Puspitasari; Sudarsono Sudarsono; Gatut Yudoyono Gatut Yudoyono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2024)
The pH measurement is essential in medicine, industry, and research, and each requires measuring instruments with different sensitivities. Measuring the pH of a solution, in principle, measures hydrogen ions in the solution. In this study, a pH sensor was designed and fabricated using macrobending multimode optical fiber. The optical fiber cladding was peeled off and replaced with a PANI-PVA (polyaniline-polyvinyl alcohol) composite layer, bent with a 2.0 and 2.5 cm diameter. The results showed that the pH sensor could measure the solution's pH linearly in the range of pH = 2 to 8.